2011
DOI: 10.1155/2011/548123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cannabinoid CB1Receptor Binding in Adolescent and Adult Rats: A Positron Emission Tomography Study Using [18F]MK-9470

Abstract: Despite the important role of cannabinoid CB1 receptors (CB1R) in brain development, little is known about their status during adolescence, a critical period for both the development of psychosis and for initiation to substance abuse. In the present study, we assessed the ontogeny of CB1R in adolescent and adult rats in vivo using positron emission tomography with [18F]MK-9470. Analysis of covariance (ANCOVA) to control for body weight that would potentially influence [18F]MK-9470 values between the two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 67 publications
(80 reference statements)
1
28
0
Order By: Relevance
“…The basis for these age- and strain-specific differences in anxiety-like behavior is unclear. The amygdala, which has been implicated in anxiogenic effects of THC and evaluation of uncertainty (Rosen & Donley, 2006; Rubino et al, 2008), differs from the hippocampus in that adolescent and adult Wistar rats display similar levels of available CBRs (Verdurand et al, 2011). All ages and strains treated with acute THC demonstrated anxiety-like behavior in at least one paradigm, indicating a nebulous anxiogenic effect of THC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for these age- and strain-specific differences in anxiety-like behavior is unclear. The amygdala, which has been implicated in anxiogenic effects of THC and evaluation of uncertainty (Rosen & Donley, 2006; Rubino et al, 2008), differs from the hippocampus in that adolescent and adult Wistar rats display similar levels of available CBRs (Verdurand et al, 2011). All ages and strains treated with acute THC demonstrated anxiety-like behavior in at least one paradigm, indicating a nebulous anxiogenic effect of THC.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that a repeated history of adolescent injections would impair later adult object discrimination but be anxiolytic in the EPM compared to vehicle groups, whereas an adult history would have no effect on later behavior. Finally, CB1R binding increases across the brain during the transition from adolescence to adulthood (Verdurand et al, 2011), but repeated treatment may result in receptor downregulation (Breivogel et al, 1999). Therefore we hypothesized that adolescent treatment with THC would cause long-term changes in CB1R receptor expression compared to adult treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic marijuana users exhibited a 20% decrease in cortical CB1 receptors compared to controls at baseline, but after a month of abstinence from marijuana, differences were no longer detectable between users and controls (Hirvonen et al, 2012). In animal models, there is an inverse relationship between CB1 receptor expression in cortical and striatal regions, such that striatal regions with more CB1 receptor expression receive input from cortical regions with less expression, and critically, the expression levels of CB1 receptors in these circuits decrease from adolescence to adulthood (Van Waes, Beverley, Siman, Tseng, & Steiner, 2012; Verdurand et al, 2011). Thus, exogenous influences of THC on these circuits could counteract typical maturational trajectories and yield changes in regions critical for decision making and addiction processes (Volkow & Baler, 2014; Volkow, Koob, & McLellan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies of rodents (Verdurand et al, 2011) and human subjects (Mato et al, 2003) suggest global increases in CB 1 R throughout early life into adolescence, at which period adult levels are generally maintained (Belue et al, 1995; McLaughlin et al, 1994; Rodriguez de Fonseca et al, 1993), but there are also reports of reduced CB 1 R expression from juvenile to adulthood that mirrors developmental changes in CB 1 R-mediated signaling (Heng et al, 2011). Some of the inconsistencies regarding the ontogenic pattern of the CB 1 R may be due to regional, as opposed to global, developmental differences in the receptor development in addition to differences in mRNA, receptor protein or receptor binding being studied.…”
Section: Neurobiology Of the Endocannabinoid Systemmentioning
confidence: 99%
“…While no study thus far has characterized the pattern and abundance of CB 1 R in the different output pathways during development, it is known that CB 1 R expression is dynamic during the course of adolescent development in different brain regions. For example, in vivo (Verdurand et al, 2011) and in vitro (Belue et al, 1995) imaging of the rat brain that revealed global enhanced CB 1 R in the cortex, also showed increased CB 1 R in other brain structures including the striatum during the transition from early adolescence to adulthood. However, other investigators have provided significant evidence for reduced CB 1 R expression and mRNA levels from juvenile to adulthood (Van Waes et al, 2012).…”
Section: Neurobiology Of the Endocannabinoid Systemmentioning
confidence: 99%